The Cytotoxicity of Daruju Mangrove (Acanthus ilicifolius) Leaf Extract as Root Canal Irrigation - Ratna Putri; Twi Agnita Cevanti; Henu Sumekar (Denta Journal Kedokteran Gigi, 2018)
Background: The cleaning and shaping of the root canal are important stages in root canal treatment. The irrigation solution needed in those stages to clean the canal from residual necrotic tissue, demtine particles, and microorganism. Irrigation solution must fulfill some criteria among others, able to solute the debris or tissue residual, has low surface tension and not toxic. Mangrove Daruju (Acanthus ilicifolius) has potency to be a alternative of the usual irrigation solution because has antibacterial effect. Purpose: The aim of this study was to examine the cytotoxicity of Daruju mangrove (Acanthus ilicifolius) as root canal irrigation against the fibroblast cell (BHK-21) culture. Materials and Methods: The samples used was fibroblast cells (BHK-21) using culture method. These samples were treated with Acanthus ilicifolius chloroform extract with several concentration. Samples were divided into 1: cell control, 2:media control, 3: 40mg/ml, 4: 50mg/ml, 5: 60mg/ml, 6: 70mg/ml,: 80mg/ml, 7: control. MTT was added, 3 minutes after that incubated for 4 hours. DMSO solution was added and then shaken, the samples were analyzed using ElISA reader with a 620 wavelength. The cytotoxiciy wa expressed by cell viability. If its is > 50%, it is declared as non toxic. Data analyzed using non parametric test (Kruskal-Wallis) followed by Mann Whitney test. Results: The Kruskal-Wallis test proved that there were significant differences in the cell viability among the treated groups. The average difference among the treated groups which were tested with Mann-Whitney test, showed a significant difference between group 1 and 5, also group 2 and group 5. Conclusions: Acanthus ilicifolius leaf chloroform extract has no cytotoxicity effect on concentration fibroblast cell (BHK-21) culture.